An Experimental Study to Evaluate the Effect of Ambient Temperature during Manual Lifting and Design of Optimal Task Parameters. Issue 1 (21st October 2011) - Singh, Ravindra Pratap; Batish, Ajay; Singh, T. P.; Bhattacharya, Anirban
Abstract In the present study, the effect of lifting task parameters on the heart rate and oxygen uptake of workers during manual lifting tasks in different ambient conditions was evaluated. The experiments conducted in two different temperature conditions showed a significantly higher oxygen uptake and heart rate in colder conditions as compared to warmer conditions. Three other factors, namely, load, lifting frequency, and vertical distance were found to significant affect the responses. Various combinations of significant factors were used to calculate oxygen uptake and heart rate. These were then compared with the safe limits as per the maximum aerobic capacity of workers. Based on these comparisons, the safe combinations were identified that can be used to design lifting tasks in varied ambient conditions. The study further concluded that lifting tasks performed in winter should have different relaxation or fatigue allowances built into the cycle time of the task to compensate for higher exertion. © 2011 Wiley Periodicals, Inc.